Respon Tanaman Cabai Besar (Capsicum annuum L.) terhadap Pengayaan Trichoderma pada Media Tanam dan Aplikasi Pupuk Boron - Dermawan, Rahmansyah; Farid B. D. R., Muh.; Ridwan Saleh, Ifayanti; Syarifuddin, Reni (Jurnal Hortikultura Indonesia, 2019)
A study was conducted to determine the response of several varieties of large chilli (Capsicum annuum L.) to Trichoderma enrichment on planting media and Boron fertilizer applications. The study was conducted from June to September 2017 at the Experimental Garden of the Faculty of Agriculture, Hasanuddin University, Makassar in the form of factorial Split Plot Design with 2 factors. Experiments were set with large chili varieties as the main plot consisting of var. Karina, var. Tombak, and var. Panex 100 F1, while the combination of Trichoderma enrichment and Boron fertilizer was set as subplots consist of 6 treatment combinations. The results show that there was a significant interaction between the treatment of varieties and Trichoderma Boron on plant height parameter and there was a significant effect of the varieties treatment on the number of productive branches and the number of fruits per plant. In addition, significant effect of the Trichoderma Boron treatment was shown in the parameters of fruit length per plant 100 HST. The interaction that gave the best results was in the treatment of Trichoderma asperellum 4 g plant-1 and Panex 100 F1 varieties on plant height of 47.77 cm. The treatment of varieties that gave the best results was Karina variety and the combination treatment of Trichoderma-Boron that gave the best results was the treatment of Trichoderma asperellum 4 g plant-1 + Boron 1 mg L-1. Keywords: Capsicum annuum L., microbe, boron fertilizer, varieties